Health related quality of life among patients with hypertension - MasrorRoudsari, daryadokht; DabiriGolchin, mahsa; Parsayekta, zohreh; Haghani, hamid (Advances in Nursing & Midwifery, 2014)
Abstract Backgroun an aim: Like other chronic diseases, hypertension is closely related with lifestyle, mental health and quality of life. The goal of this study was Determination of health related quality of life in hypertensive patients. Materials and Methods: The study was Descriptive, samples were chosen by using convenience sampling and according to characteristics of samples and Their willingness to participate in the study. The data gathering tools in this study were Social and personal information (demographic) forms, and health-related quality of life questionnaire. (SF-36). Clinical research environment at selected hospitals affiliated to Tehran University of Medical Sciences consist of Hazrat Rasoul Akram Hospital, Imam Khomeini Hospital, and Shahid Rajai. To determine the relationship between The main variable and demographic variables and use ANOVA and T-Test, we entered variables that were significant in our regression model. Findings: 264 patients with hypertension take part in this study. Most of Participants were male and their age was in range of 40-60 years old. Mean of quality of life among hypertensive patients was 55. 33. There was a statistically significant relationship between quality of life and job, information about the disease, other chronic diseases and medication groups. Conclusion: The study shows that there health related quality of life is low in hypertensive patients. Key words: health related quality of life, hypertension REFERENCES Ahangari M., Kamali M., Arjomand Hesabi M.( 2008) [A study of quality of life among older people with hypertension. Journal of Salmand ]. 3(7)26-32.(Persian). Amar J, Chamontin B, Genes N, Cantet C, Salvador M. and Cambou JP. (2003) Why is hypertension so frequently uncontrolled in secondary prevention? Journal of Hypertension . 21(6) 1199–1205. Braunwald, E., Fauci, A.S., Kasper, D.L., Hauser, S.L., Longo, D & Jamason, J.L. (2001). Harrison’s Principles of Internal Medicince . NewYork: McGraw-Hill Professional Publishing; 15th edition. Burkhardt M., Nathalien A.(1998) Ethics and Issues in Contemporary Nursing .Albani Bonn. Burstrom K, Johannesson M, Diderichsen F.( 2001) Health-related quality of life by disease and socio-economic group in the general population in Sweden. Health Policy .55(1)51– 69. Carrasco-Garrido , P., Diez, J.d M., Gutierrez, J. R et al.( 2006) Negative impact of chronic obstructive pulmonary disease on the health related quality of life of patients. Results of the EPIDEDOC study. Health and Quality of Life Outcomes . 4(31) 1-9. Collins E, Langbein WE, Dilan-Koetje J, et al.( 2004) Effects of exercise training on aerobic capacity and quality of life in individuals with heart failure. Heart and Lung . 33(3) 154-61. Cote I.,Farris K.,Feeny D. 2003. Is adherence to treatment correlated with health related quality of life? Quality نشریه دانشکده پرستاری و مامایی یپوهنملفشرختبا. ا یمرب یملطسرتبا یگنزدت ی یکسر / 17 ر مف د ب of life research 12.pp. 621-633. Esmaeili Z.,Ziabakhsh Tabari SH.,Vaezzadeh N.,Mohammadpour Tahamtan R.A( 2007)[Quality of life after coronary artery bypass grafting in Sari city, 2005-2006]. Journal of Mazandaran University of Medical Sciences . 17(61)170-174.(Persian ). Fadaee Aghdam N., Masror Rodsari D., Rafii F., Hoseini A.F.( 2012)[ Relationship between health related quality of life and respiratory symptoms in patients with COPD ]. Thesis for Master degree of nursing. Iran University of Medical Sciences.(Persian). Ferrans C. E.,Powers M. J.( 1985) Quality of life index : Development and psychometric properties. ANS Advances in Nursing Science . 8(1)15-24. Fredericks E. M., Magee J. C., Opipari-Arrigan L., et al (2008) Adherence and health related quality of life in adolescent liver transplant recipients. Pediatric Transplantation .12(3)289-99. Ghanbarian A Rahmani M Sarafzadeh A Azizi F( 2003) Hypertension distribution in Tehranian adult population Tehran lipid and glucose study. Iranian Journal of Endocrinology and Metabolism .5(Sup 4) 425-435.(Persian). Gusmão JL, Mion Jr. D, Pierin AMG. (2009) Health-related quality of life and blood pressure control in hypertensive patients with and without complications. Clinics (Sao Paulo).64(7) 619-28. doi: 10.1590/S1807-59322009000700003 Jabal Ameli, Sh. Neshat Doost, H. Moulavi, H.( 2010)[ Effectiveness of cognitive-behavioral stress management therapy intervention on quality of life and and blood pressure in female patients with hypertension]. Scientific Journal of Kurdistan University of Medical Sciences (SJKU). 15 (2) 88-97( Persian)URL http:// sjku.hbi.ir/browse.php?a_code=A-10-1-247&slc_lang=en&sid=1 King C.R., Hinds P.S. (1998) Quality of life: From Nursing and Patients Perspectives: Theory Research Practice . Jones and Bartlett publishers. Li C, Niu S.( 2005) Quality of life of patients having renal replacement therapy. Journal of Advanced Nursing . 51 (1)15-21. Martin, A., Moro, J.M.R.-G., Jose L. et al ( 2008) Health related quality of life in out-patients with chronic obstructive pulmonary disease in daily practice: the VICE Spanish study. International Journal of Chronic Obstructive Pulmonary Disease , 3(4)683-692. Mena-Martin FJ, Martin-Escudero JC, Simal-Blanco F et al .( 2003) Health-related quality of life of subjects with known and unknown hypertension: results from the population-based Hortega study. Journal of Hypertension . 21(7)1283–1289. Mohammad pour Y, Haririan H, Moghaddasian S, Ebrahimi H.(2008) Surveying the quality of life and its dimensions among the type 2 diabetes patients referred to the Diabetes center of Tabriz university of medical sciences. Journal of Nursing and Midwifery Urmia University of Medical Sciences.6(1) 26-37. ( Persian). URL http://unmf.umsu.ac.ir/browse.php?a_code=A-10-2-71&slc_lang=fa&sid=1 Montazeri A, Gashtasebi A, Vahdaniani M, Ganalek B.( 2005) The short form health survey study of the Iranian version. Quality of Life Researches . 14(3) 875-82. Najmi B, Ahadi H, Delavar A, Hashemipoor M)2007)[ The effectiveness of multidimentional psychological treatment in enhancing the adherence to medical treatment in adolescents with type 1 diabetes]. Journal of Research in Behavioural Sciences . 5(2) 127-136(Persian). Nunes M L.(2001)The relationship between quality of life and adherence to treatment. Current Hypertension Reports .3(6)462-465. Orem D.E.( 2001) Nursing Concepts of Practice , 6th ed, USA: mosby Inc. Pais-Ribeiro JL.( 2004) Quality of life is a primary end-point in clinical settings. Clinical Nutrition . 23(1) 121-30. Ritcher A., Anton S.E., Koch P. 2003. The impact of reducing does frequency on health outcomes. Clin 1392 ناتسمز ،83 هرامش ،23 هرود / 18 ناراکمه و یرسدور رورسم تخدایرد Ther .25.p.2307. Rulxing ,Y. ,Limei,Y. ,Yuming,C. ,Dezha, Y.2006.prevalence, awareness,treatment, control and risk factor of hypertension in theGuangxi Hei Yi Zhuang and Han populations. Hypertensions 29(6) 423-432. Shabany-Hamedan M., Mohmmad-Aliha J., Shekarabi R., Hosseini AF.(2010) [The relationship between medication adherence and quality of life in Renal Transplant Patients]. Iran Journal of Nursing . 23 (67) 29-34.( Persian). Simpson E, Pilote L. 2005.Quality of life after acute myocardial infarction: a comparison of diabetic versus non-diabetic acute myocardial infarction patients in Quebec acute care hospitals. Health and Quality of Life Outcomes 2005, 3:80 doi:10.1186/1477-7525-3-80 .available from: http://www.hqlo.com/content/3/1/80; open access Smeltzer,Suzanne,.Bare, G.,Brenda, Hinkle,.L, Janice,. Cheever,H., Kerry. (2010). Brunner and Suddarth’s Textbook of Medical Surgical Nursing . 12th edition. Lippincott Williams & Wilkins. Sotoude Asl, N., Neshatdoost, H.T., Kalantari, M., Talebi, H., Khosravi, A.R.( 2010) [Comparison of the effectiveness of cognitive behavioral therapy and medication on the quality of life in the patients with essential hypertension] . Koomesh Scientific journal of Semnan University of Medical Sciences .11(4 [ serial36]) 294-301. Persian Steven P., Gould D. (1997) Non-adherence with medications in organ transplant patients: a literature review. Journal of Advanced Nursing .26(5)968-977. URL http://jmums.mazums.ac.ir/browse.php?a_code=A-10-1-279&slc_lang=fa&sid=1 Vahdani Nia MS, Goshtasebi A, Montazeri A, Maftoon F (2005)[ Health-related quality of life in an elderly population in Iran: A population-based study. Payesh Journal .4(2)113-120(Persian). World Health Organization.2001. High light on health in Switzerland.